PROBLEMATIKA PENGELOLAAN ANGGARAN PADA SEKRETARIAT BAITUL MAL KABUPATEN ACEH TENGAH TAHUN ANGGARAN 2018-2020 - Raimadani Raimadani (Journal of Political Sphere, 2022)
Baitul Mal is a government organization that manages the assets of Muslims, namely zakat, infaq, shadaqah and other religious assets, this is one of the regional and district/city incomes. In 2018-2020 the management of zakat, infaq, shadaqah and other religious assets in Baitul Mal, Central Aceh can still be said to be ineffective due to the low absorption of the budget, thus eliminating the benefits of spending because the budget is not utilized optimally, resulting in budget errors that continue to increase every year starting from 2018- 2020. 2020. This study aims to analyze budget management at the Baitul Mal secretariat of Central Aceh Regency in 2018-2020 and identify factors that hinder the budget management process at the Baitul Mal secretariat of Central Aceh Regency in 2018-2020. The theory suggested in this study is the theory of budget politics proposed by James A.F Stoner, namely planning, organizing, implementing and monitoring. The method used is descriptive qualitative. The results of the study show that budget management in Baitul Mal, Central Aceh Regency still has constraints so that the budget absorption is very low, this is due to several factors, namely, the criteria for the poor and mustahiq requirements that are very strict for the people of Central Aceh, The organizational structure of Baitul Mal, Central Aceh Regency is still incomplete, namely the absence of a sharia supervisory board and a change in the mechanism in the budget management process, previously zakat infaq shadaqah and other religious assets were managed independently by the Regency Baitul Mal but now it has become PAD (Regional Original Income). ) which must follow budget management in accordance with the regional budget management flow.